Schumpeter meets Goldilocks: The scarring effects of firm destruction - Beatriz González; Enrique Moral-Benito; Isabel Soler (SERIEs - Journal of the Spanish Economic Association, 2023)
This paper uncovers an inverted U-shaped relationship between firm exit and total factor productivity (TFP) growth using Spanish data. At low levels of firm exit, Schumpeterian cleansing effects dominate and the effect of firm destruction on TFP is positive, but when exit rates are very high, this effect turns negative. In order to rationalize this finding, we build on Asturias et al. (Firm entry and exit and aggregate growth, Technical report, National Bureau of Economic Research, 2017) and develop a model of firm dynamics with exit spillovers calibrated to match the nonlinearity found in the data. This reduced-form spillover captures amplification effects from very high destruction rates that might force viable firms to exit, for example, due to disruptions in the production network and a generalized contraction in credit supply. Armed with the calibrated model, we perform counterfactual scenarios depending on the severity of the shock to firm's outcomes. We find that when the shock is mild and firm destruction rates at impact are similar to those observed during the Global Financial Crisis (GFC), TFP growth increases, and the recovery is faster. However, when the shock is severe and firm exit is well above that of the GFC, TFP growth decreases, since high-efficiency firms are forced out of the market, which makes the recovery much slower.
Keywords: E22; G33; M21; O47; 330; Firm dynamics; Firm exit; Productivity; COVID-19